Environment- and Genotype-Dependent Irrigation Effect on Soybean Grain Yield and Grain Quality - Maja Matoša Kočar; Marko Josipović; Aleksandra Sudarić; Hrvoje Plavšić; Ivica Beraković; Atilgan Atilgan; Monika Marković (Applied Sciences, 2022)
This four-year study with four elite soybean lines with different maturities was conducted to investigate the impact of deficit (a field water capacity, or FWC, of 60%) and full irrigation (an FWC of 80–100%) on soybean grain yield and grain quality (grain protein and oil contents and crude protein and oil yields), depending on the environmental conditions and genotype. Overall, the irrigation effect was positive for the grain yield and grain protein content but negative for the grain oil content. The differences between the full and deficit irrigation were only 2.9% for the grain yield, 2.8% for the crude protein yield and 1.7% for the crude oil yield. The results indicate that deficit irrigation could be the best option for optimizing soybean production in environments similar to the tested one. In such conditions, further rationalization of soybean production could be achieved by choosing the C2 genotype (0 maturity group), which, combined with deficit irrigation, had the highest grain, crude protein and crude oil yields.